Targeting Inflammation and Inflammatory-Related Diseases with Natural Bioactives - Maione, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Inflammation is a complex biological response to injury as a result of different stimuli such as pathogens, damaged cells, or irritants. Inflammatory injuries induce the release of a variety of systemic mediators, cytokines, and chemokines that orchestrate cellular infiltration, consequentially bringing about the resolution of inflammatory responses and the restoration of tissue integrity. However, persistent inflammatory stimuli or the disregulation of the mechanisms of the resolution phase can lead to chronic inflammation and inflammatory-based diseases. Nowadays, commercially approved anti-inflammatory drugs are represented by nonsteroidal anti-inflammatory drugs (NSAID); glucocorticoids (SAID); and, in some cases, immunosuppressant and/or biological drugs. These agents are effective for the relief of the main inflammatory symptoms. However, they induce severe side effects, and most of them are inadequate for chronic use. Starting from these premises, the demand for new, effective, and safe anti-inflammatory drugs has led research in new therapeutic directions. The recent and emerging scientific community slant is oriented towards natural products/compounds that could represent a boon for the discovery of new active molecules and for the development of new drugs and potentially useful therapeutic agents in different inflammatory-related diseases. We hope that it will stimulate the interest of the scientific community involved in studying the effects of natural and synthetic compounds in different fields of interest such as acute and chronic inflammation, inflammatory pain, inflammation-related diseases (e.g., autoimmune diseases), amongst others.